Analysis of Umkm Warkop Bistur's Strategy in Increasing Revenue - Nuralifa Salsabila Muhtar; Jumawan Jumawan; Rifqi Galuh Putra Ramadhan; Raditya Raffi Firmansyah; Indah Deya Ramadhan; M Reyhan Riyandito (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2023)
Warkop is currently one of the fastest growing companies. Considered a casual restaurant. One of the warkop located near the Bhayangkara University campus is Bistur Warkop. This research uses qualitative research methods, namely. observation and interview. This research was conducted at Warkop Bistur which is located next to Bhayangkara University, Greater Jakarta. The data collection techniques used in this study were observation and interviews. The motivation for the owner of Warkop to build his business is so that Warkop Bistur can be used as a place of learning for Bhayangkara students. Warkop Bistur is its strategic location and friendly prices with students so that it can attract customers who are mostly students of Bhayangkara University.